2019
DOI: 10.1017/wet.2018.97
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and Frequency of Glyphosate-Resistant and Glyphosate-Tolerant Weeds in Soybean-producing Edaphoclimatic Microregions in Brazil

Abstract: Glyphosate-resistant (GR) and glyphosate-tolerant weeds cause considerable yield losses and represent a growing threat to soybean production systems. Despite the relevance of this topic, few studies have evaluated the dispersal of these species in Brazil. The objective of this study was to evaluate the dispersal and frequency of known GR and glyphosate-tolerant weeds in soybean-producing microregions. A total of 2,481 interviews were conducted in different regions of Brazil. The interviews were stratified amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 18 publications
0
35
0
5
Order By: Relevance
“…The occurrence of weeds during the off-season may vary depending on the specific weather and climate conditions for each region, besides being influenced by factors related to soil preparation, the history of herbicides sprayed, and crops cultivated in the area. The continuous use of glyphosate herbicide in Brazilian agriculture has favored the increased frequency of resistant biotypes and herbicide tolerant species in the principal soybean producing regions of this country (Lucio et al 2019). In Brazil, currently there are 7 species of weeds resistant to this herbicide, and among them fleabane (Conyza spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of weeds during the off-season may vary depending on the specific weather and climate conditions for each region, besides being influenced by factors related to soil preparation, the history of herbicides sprayed, and crops cultivated in the area. The continuous use of glyphosate herbicide in Brazilian agriculture has favored the increased frequency of resistant biotypes and herbicide tolerant species in the principal soybean producing regions of this country (Lucio et al 2019). In Brazil, currently there are 7 species of weeds resistant to this herbicide, and among them fleabane (Conyza spp.…”
Section: Introductionmentioning
confidence: 99%
“…; Asteraceae), sourgrass (Digitaria insularis [L.] Mez ex Ekman; Poaceae), and goosegrass (Eleusine indica [L.] Gaertn. ; Poaceae) stand out as species with wide geographic distributions (Heap & Duke 2018;Lucio et al 2019). The traffic of agricultural machines and implements, as well as seeds from the border regions with other countries, principally Argentina, Uruguay, and Paraguay, which are the main entry points for new resistant species, allow resistant species such as smooth pigweed (Amaranthus hybridus L.; Amaranthaceae) and johnsongrass (Sorghum verticiliflorum [L.] Pers.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey showed that wild poinsettia is present in 20 to 40% of all soybean fields in Brazil, especially in Paraná and Rio Grande do Sul states [22]. Several intrinsic characteristics have allowed wild poinsettia to thrive under no-till systems, such as large seeds, short-day requirement for flowering, and ability to produce up to four generations a year [23]. In soybeans, each day of wild poinsettia-crop coexistence can represent a yield loss of 5.1 kg ha -1 [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, the area cultivated with tetraploid Italian ryegrass has been increasing in the Southern Brazilian fields due to the occurrence of diploid glyphosate-resistant populations, and its characteristics such as higher yield of pasture and nutritive value compared to diploid plants (Oliveira et al 2014). Currently, diploid glyphosate-resistant populations of Italian ryegrass can be found in approximately 6.03 million•ha -1 , a critical scenario for management in cultivated fields in which the glyphosate herbicide has been frequently used, with cases of up to four applications in the same cultivation area (Lucio et al 2019).…”
Section: Introductionmentioning
confidence: 99%